THE INFLUENCE OF SELF-EFFICIENCY, PROACTIVE PERSONALITY AND LOCUS OF CONTROL ON INTEREST IN ENTREPRENEURSHIP - Silviana , Silviana; Widjaja, Oey Hannes; Budiono, Herlina (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study was to determine the effect of self-efficacy, proactive personality, and locus of control on interest in entrepreneurship with entrepreneurship education as a moderating variable. Non-probability sampling was the sampling technique used for this study, and the number of samples was 142 respondents which was collected by distributing questionnaires via Google Forms. This study explains that 1) self-efficacy can be used to positively predict entrepreneurial interest; 2) proactive personality can be used to positively predict entrepreneurial interest; 3) locus of control can be used to positively predict entrepreneurial interest; and 4) entrepreneurial education moderates the effect of efficacy and self-interest in entrepreneurship.